TEKNIK PEMERIKSAAN KEANDALAN STRUKTUR RANGKA ATAP BAJA: TEKNIK PEMERIKSAAN KEANDALAN STRUKTUR RANGKA ATAP BAJA - Abdillah, Rifqi Aulia; Setiawan, Dedi Budi; Supriyo; Ariyanto, Arief Subakti; Pamungkas, Nur Setiaji (Bangun Rekaprima, 2025)
Damage to the roof frame construction can have an impact on other components, for example if the roof frame sags resulting in the roof covering becoming loose resulting in a leak, the leak can impact the ceiling, causing moldy damage to the worst case, collapsing. So it is necessary to ensure that the roof frame construction is always in a reliable condition, so that it does not endanger the building occupants. The method used in this research is a case study method, a model of the damaged steel roof frame construction will be made, Then a visual inspection will be carried out until further inspection. Based on the results of a visual inspection of the truss frame construction, it was found that there was a deflection in the lower frame of 4mm, there was rust which reduced the thickness of the elbow profile by 0.51mm, and the loss of some of the bolt connections was 20bh. The results of the inspection were then carried out with a strength analysis, it was found that based on the deflection results it was still below 9.33 mm, it was still safe, based on rust damage, a strength reduction of 13.31% was obtained, while based on the loss of some of the bolted connections, a strength reduction of 23.81% was obtained. Then a direct loading test was carried out on the construction of the truss frame after it had been conditioned to experience damage, capable of withstanding a maximum point load of 249 kg, where the test results experienced a decrease in strength from the plan and were still greater than the inspection results. So it can be concluded that the method for checking the construction condition of steel truss frames for deflection, rust conditions and joints can be used as a guide because the results are close to the actual conditions. The intensity of damage that occurred in the truss frame construction was categorized as light damage, because the decrease in strength that occurred was 23.81% smaller than 35%.